(untitled) (Anwer Khan Modern Medical College Journal, 2019)
Occurrence of acardiac twin is due to twin reversed arterial perfusion sequence (TRAP) occurring early in embryogenesis. There is vascular communication between the twins in monozygotic twins. The vascular communication in acardiac twin is different, in that, the acardiac twin receives blood supply from other twin pump through umbilical artery. The blood in the umbilical artery is mostly deoxygenated. Hence it leads to secondary organ atrophy. Upper body does not develop at all, hence missing heart and head. All the blood supply to the acardiac twin is derived from the pump twin. The acardiac twin develops only lower part of the body or just a mass of tissue. Hence, the mortality for acardiac twin is 100%. Anwer Khan Modern Medical College Journal Vol. 10, No. 1: Jan 2019, P 89-91